2012
DOI: 10.5581/1516-8484.20120029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytokine levels and metabolic parameters of stored platelet concentrates of the Fundação Hemominas, Belo Horizonte, Brazil

Abstract: BackgroundProlonged storage of platelets could improve availability and logistical management and decrease wastage. Immunobiochemical methods can be used to guarantee the quality of platelets after prolonged storage.ObjectiveThe aim of this study was to compare storage-related changes in buffy coat-derived platelet concentrations versus platelet-rich plasmal.MethodsUnits of whole blood were drawn using a quadruple-bag blood container system. Platelet-rich plasma and buffy coat prepared from whole blood followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
3
9
1
3
Order By: Relevance
“…In this issue of the journal, Costa et al present data on CD42b, CD62p (P-selectin), and cytokines IL-1b, IL-6, IL-8, and TNF-alpha. ( 6 ) In some respect, this study is similar to the earlier study by Metcalfe et al since P-selectin was measured in both studies. In contrast to the results of the study by Metcalfe et al, Costa et al did not observe higher levels of P-selectin in PRP PCs than in BC-PC.…”
supporting
confidence: 89%
“…In this issue of the journal, Costa et al present data on CD42b, CD62p (P-selectin), and cytokines IL-1b, IL-6, IL-8, and TNF-alpha. ( 6 ) In some respect, this study is similar to the earlier study by Metcalfe et al since P-selectin was measured in both studies. In contrast to the results of the study by Metcalfe et al, Costa et al did not observe higher levels of P-selectin in PRP PCs than in BC-PC.…”
supporting
confidence: 89%
“…These findings in RBC products were generally consistent with our results that cytokine levels of IL-1β, IL-8 and RANTES were significantly decreased by prestorage leukoreduction during the storage. In contrast, remarkable elevation of IL-1β, IL-6, IL-8 and TGF-β1 levels was seen during the process of storage in PCs [ 28 , 29 ]. Furthermore, it was reported that several cytokines, including RANTES, TGF-β1, IL-27, as well as soluble OX40 ligand (sOX40L), also a member of the TNF family and being associated with the inhibition of IL-6, IL-10 and IL-12 [ 30 ], were significantly increased during the storage of PHs [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han demostrado que el índice de torbellino o swirling en concentrados derivados de capa leucocitaria disminuyó después del séptimo día, y que en concentrados obtenidos de plasma rico en plaquetas empezó a decrecer significativamente a partir del quinto día (20).…”
Section: Discussionunclassified